Types and Characteristics of Code-switching in Twitter Posts by Humanities Students of Universitas Sumatera Utara - Fiesta Sinaga, Tantiara; Sinambela, Berlian Hasian Keyla; Sembiring, Inggrid Gavrila Beru; Rangkuti, Rahmadsyah (Linguistic, English Education and Art (LEEA) Journal, 2025)
This study investigates the types and characteristics of code-switching employed by students from the Faculty of Humanities at Universitas Sumatera Utara (USU) in their Twitter posts. Drawing on Gumperz’s (1982) conversational functions, the research explores how code-switching operates as a communicative strategy rather than a random alternation between Indonesian and English. The data were collected from naturally occurring tweets and analyzed qualitatively. The findings reveal that intra-sentential switching is the most dominant type, reflecting high bilingual competence and a fluid integration of English into Indonesian discourse. Code-switching among USU Humanities students also exhibits distinctive pragmatic traits—English is frequently used for emphasis, emotional expression, and message qualification, while Indonesian maintains interpersonal warmth and contextual familiarity. Unlike patterns found in Jakarta youth discourse, their switching is content-driven and cognitively motivated, functioning as a tool for nuanced expression rather than identity display. These characteristics highlight a unique bilingual style rooted in intellectual engagement and reflexive awareness, suggesting that academic bilingualism fosters a sophisticated, meaning-oriented mode of linguistic hybridity. Keywords: Code-switching; Sociolinguistic; Twitter